2021
DOI: 10.6061/clinics/2021/e3039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transcutaneous electrical tibial nerve stimulation for the treatment of overactive bladder: a multi-arm randomized controlled trial with blinded assessment

Abstract: To compare the effectiveness of tibial nerve transcutaneous electrical nerve stimulation (TENS) for an overactive bladder, considering the sites of application and frequency of attendance. METHODS: This multi-arm randomized controlled trial enrolled 137 adult women (61.0±9.0 years) with overactive bladder from a university hospital. They underwent 12 sessions of 30-min TENS application and were assigned to five groups: one leg, once a week (n=26); one leg, twice a week (n=27); two legs, once a week (n=26); two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…We used non-invasive (transcutaneous) electrical stimulation to treat OAB symptoms and yielded good results as a previous study by Pierre and colleagues reported that invasive (percutaneous) electrical stimulation significantly treated OAB symptoms [21]. The effectiveness of TTNS in the current study established that transcutaneous application of electrical stimulation can be preferred over percutaneous stimulation for OAB symptoms because it is more comfortable for the patients.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We used non-invasive (transcutaneous) electrical stimulation to treat OAB symptoms and yielded good results as a previous study by Pierre and colleagues reported that invasive (percutaneous) electrical stimulation significantly treated OAB symptoms [21]. The effectiveness of TTNS in the current study established that transcutaneous application of electrical stimulation can be preferred over percutaneous stimulation for OAB symptoms because it is more comfortable for the patients.…”
Section: Discussionsupporting
confidence: 60%
“…It was also supported by the study done by Pierre ML in which they applied TTNS once a week to treat OAB symptoms. Their study showed that only once-a-week application of TTNS did not alter the outcomes of the treatment or impede the recovery of the symptoms [21].…”
Section: Discussionmentioning
confidence: 98%
“…The amplitude was adjusted to the level that produced painless paresthesia in each patient according to their tolerance. PTNS was applied for 30 min [20]. Patients who did not receive six sessions of treatment or who missed 3-to 4-day intervals were excluded from the study.…”
Section: Interventionmentioning
confidence: 99%
“…Another thing to pay attention is whether stimulation is better given in one or both legs. In one study, the stimulation of one leg was adequate to relieve OAB symptoms, except for nocturia, but the best results were seen with the two-leg protocol [ 56 ]. Therefore, the use of T-TNS should be tailored to the specificity of the symptoms described by the patient.…”
Section: Electrical Stimulation Modalitiesmentioning
confidence: 99%